(3eSCdI HjJ GdeGds
(3ChdgG (B:s
(3GdTGaYjI PcQhG Cf GdHjY HGWd hCf GdMce Hg dGjUM s
(3BNQgG (B:s
(3hcPdc WGdH GdYde hGdhGYX GdPj jYX GdfGS HGdMb hGdPj ojYdege GfJgi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3Gdabg GdTGaYjs